KAJIAN STRATEGI PENGEMBANGAN INDUSTRI PENGOLAHAN IKAN DI KOTA PALOPO PROVINSI SULAWESI SELATAN - Marwati, Ummi Maksum; Wiryawan, Budy; Lubis, Ernani (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The fishing industry is one of industry that has the potential to be developed. Specifically Indonesian fisheries potential quite large and can be an opportunity to build fish processing industry. Palopo town has a structure that embodies the policy center that strengthen agro industry activities, trade and services as well as tourism and other municipal activities optimally. In addition, the fisheries subsector is featured subsector in Palopo. Therefore, the study of fish processing industry development in Palopo done, it aims to determine the appropriate strategy for Palopo conditions. The analytical method used are qualitative descriptive and SWOT. Results by using SWOT analysis concluded that the strategies that can be offered were 1) strengthening and developing an integrated fish processing group from local coastal community; 2) utilizing and maintaining the cold storage, ice factory, and fish processing building; 3) expanding the market especially processed fish products; and 4) easy administration access for local fish industry.